If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 7 + -1(3x) = 4 + (9x) Remove parenthesis around (3x) 7 + -1 * 3x = 4 + (9x) Multiply -1 * 3 7 + -3x = 4 + (9x) Solving 7 + -3x = 4 + (9x) Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '(-9x)' to each side of the equation. 7 + -3x + (-9x) = 4 + (9x) + (-9x) Combine like terms: -3x + (-9x) = -12x 7 + -12x = 4 + (9x) + (-9x) Combine like terms: (9x) + (-9x) = 0 7 + -12x = 4 + 0 7 + -12x = 4 Add '-7' to each side of the equation. 7 + -7 + -12x = 4 + -7 Combine like terms: 7 + -7 = 0 0 + -12x = 4 + -7 -12x = 4 + -7 Combine like terms: 4 + -7 = -3 -12x = -3 Divide each side by '-12'. x = 0.25 Simplifying x = 0.25
| (u+6)(u+6)=2u^2+6u+64 | | [13x-8]=0 | | 3-z/4=8 | | -9t+15t=36 | | r/3-2=-5 | | [10a-17]=11 | | 36b^2+12b+1=0 | | 2(x+10)= | | -3.2w+-2=-4.5 | | -.1t^2+1.9t=10 | | 0.6c=360 | | 1/2(5x-6)-18=14 | | -.1t^2+1.9t=0 | | [3z+7]=11 | | (5/6)-(2x/2x+3)=(19/6) | | [2y-3]=11 | | -47h+12h=28 | | -18=9n-5n+10 | | [x-5]=11 | | 2+4/5y=-7+2/5y | | 100x=6x^2+4x | | [10a]=11 | | [3z]=11 | | 1x+60=4x | | [2y]=11 | | m+m+32= | | 21y=(-205)+75+47y | | 64=4a | | 15x-7x=(-52)-5x | | r+25+73= | | 9x^3y+48x^2y+64xy=0 | | x=9(9,6) |